The first Soviet collaborators in Lithuania in the summer of 1940: opportunists seeking social advancement or ideological communists? (The case of Šiauliai County) - Tumavičius, Andrius (Genocidas ir rezistencija, 2026)
This article examines one aspect of the issue of collaboration with the Soviets in Lithuania – cooperation with the regime during the first months of the occupation. Using the prosopographical method, it analyses a specific political group: individuals who joined the Communist Party in Šiauliai County in the summer of 1940. The study explores their motivations, social background, professional activities, political engagement and so on. The findings are then used to construct a collective biography of the first collaborators. The aim is to answer the question of whether these individuals were ideological communists or opportunists seeking social advancement. The research revealed that no unequivocal answer can be given to this question. The analysis provides grounds for arguing that, in the summer of 1940, people were encouraged to join the communist ranks by a combination of what Stanley Hoffmann termed ‘servile’ and ‘ideological’ collaborationism: a conscious willingness on the part of some members of society to serve the enemy in pursuit of personal gain, together with the deliberate support of a foreign power perceived as a catalyst for desirable domestic change. However, to refute or confirm this insight, further research on the same political group across a broader region is required. It was established that the majority of the research sample consisted of mature individuals who had already started families. This suggests that the decision to become a collaborator was not the product of youthful energy or idealism, but rather a deliberate choice driven by self-interest, i.e. to take advantage of emerging opportunities and secure prosperity for oneself and one’s family. It is also important to note that the pursuit of personal well-being was closely intertwined with the Soviet-proclaimed idea of striving for ‘the people’s welfare’. The study produced the following collective portrait of the people who joined the Communist Party of Lithuania in Šiauliai County during the summer of 1940: a married, 30-year-old Lithuanian man from the poorest strata of society, living in a city or small town, with a primary education, earning a living through wage labour, having had no ties to the Communist Party prior to 1940, and becoming involved in the newly established local administrative apparatus during the first months of the Soviet occupation.